2023
DOI: 10.1088/1748-605x/acfbd0
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and antibacterial properties of zinc-doped Ta2O5 nanorods on porous tantalum surface

Anqi Cai,
Hairong Yin,
Cuicui Wang
et al.

Abstract: This paper focuses on the preparation of Zn2+-doped Ta2O5 nanorods on porous tantalum using the hydrothermal method. Porous tantalum is widely used in biomedical materials due to its excellent elastic modulus and biological activity. Porous tantalum has an elastic modulus close to that of human bone, and its large specific surface area is conducive to promoting cell adhesion. Zinc is an important component of human bone, which not only has spectral bactericidal properties, but also has no cytotoxicity. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…NaRen et al [42] implemented ion exchange techniques to integrate Mg 2+ and Ca 2+ into the interlayers on titanium foil surfaces. This process, when compared to Na + -enriched titanate nanostructures, markedly increases protein adsorption due to the presence of divalent ions (Mg 2+ , Ca 2+ ), thus enhancing both the adsorption and differentiation capacities of rBMSCs [43]. Using various analytical methods such as ALP, EDX, FTIR and XRD, we demonstrated that calcium ions are superior to magnesium ions in promoting cell differentiation.…”
Section: Introductionmentioning
confidence: 95%
“…NaRen et al [42] implemented ion exchange techniques to integrate Mg 2+ and Ca 2+ into the interlayers on titanium foil surfaces. This process, when compared to Na + -enriched titanate nanostructures, markedly increases protein adsorption due to the presence of divalent ions (Mg 2+ , Ca 2+ ), thus enhancing both the adsorption and differentiation capacities of rBMSCs [43]. Using various analytical methods such as ALP, EDX, FTIR and XRD, we demonstrated that calcium ions are superior to magnesium ions in promoting cell differentiation.…”
Section: Introductionmentioning
confidence: 95%